Cocoa Bean Fermentation in Ivory Coast: Processes, Challenges, and Innovations for Uncompromising Market Quality - Ibourahema, Coulibaly; Ahossi, Konan Kouakou; Athanase, Kra Kouassi; Clément, Kouassi Kouassi; Rodrigue, Voko-Bi Don; Maxwell, Beugré Avit; Ibrahim, Konaté (European Journal of Applied Sciences, 2025)
Ivory Coast accounts for approximately 40% of global cocoa production, with an annual average output of 2 million tons, consolidating its position as the world’s leading producer. Over 6 million people nearly one-quarter of the Ivorian population depend directly or indirectly on this sector. The quality of cocoa beans, particularly their degree of fermentation, plays a decisive role in determining the competitiveness of Ivorian cocoa on an international market that is increasingly demanding in terms of sensory attributes, food safety, and environmental sustainability. Fermentation, which contributes 25 to 30 % of the post-harvest added value, is a critical step that shapes the organoleptic properties (aroma, color, texture) of the final chocolate product. However, nearly 35% of exported beans exhibit defects related to incomplete or poorly managed fermentation, leading to economic losses estimated between 10 % and 30 % of the potential export value. These shortcomings are largely due to the heterogeneity of fermentation practices, in-adequate equipment, limited knowledge of microbial dynamics, and insufficient incentives for quality enhancement. This article explores current trends in cocoa bean fer-mentation in Ivory Coast through five key dimensions: 1) scientific and microbiological foundations of the process; 2) traditional practices and their limitations; 3) market requirements and economic challenges; 4) emerging technological and organizational innovations; and 5) future prospects for standardization and traceability. The study underscores the urgent need for national quality standards and differentiated valorization mechanisms for well-fermented beans, which can command premium prices of up to US/$300 per ton. Strengthening the technical capacity of local stakeholders, modernizing fermentation infrastructure, and integrating research-based innovations are essential levers to ensure the high marketability of Ivorian cocoa.